Need Analysis for English Reading Teaching Materials in Vocational School Based on Digital Applications - Oktariyani, Oktariyani; Rasyid, Yumna; Dewanti, Ratna; Im, Hyunbim; Semyanov, Larra (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
This study aims to determine the need for English reading teaching materials for Vocational High School students majoring in Fashion Design, and to determine the need for English reading skills in the world of work. Data were obtained from questionnaires and interviews. The subjects studied were students of SMK Rahmatutoyibah Gunung Kaler, grade X majoring in Fashion Design, and grade X English teaching materials for SMK. This research was conducted with a mixed-method design. The data were collected through questionnaires and structured interviews. This questionnaire is based on the SMK English learning curriculum. The results of this study indicate that Vocational High School students majoring in fashion need teaching materials that are by their majors, namely reading materials related to the fashion department as well as material that introduces a lot of the industrial world and can support the field they are engaged in. Furthermore, Grade X Vocational School students majoring in Fashion Design need English reading learning media to encourage easy understanding of English reading material, namely media in the form of interesting and contemporary digital applications. Furthermore, the need for the world of work for their English reading skills requires skilled workers who have good English reading skills, which include the ability to read manual books, the ability to read company regulations, the ability to read travel documents, the ability to read English messages, the ability to reading notes, the ability to read e-mails, the ability to read employment contracts, and the ability to read cooperation agreements.